Criticism of Neo-liberalism and Ahistorical Manifestos - Hanuš, Jiří (Dějiny – teorie – kritika, 2012)
Jiří Hanuš critically reacts to the contribution of Pavel Baloun, Jan Gruber, Jan Mareš, and Vít Strobach ‘O výuce historie za kapitalismu a o mluvících hlavách’ (On Teaching History Under Capitalism and On Talking Heads). The author off ers some alternative views regarding the teaching of history, potential employment opportunities for graduates in this fi eld, and the impact on general view of history of media-promoted notions created by historians.